Foreigner (peregrinus) in Ancient Rome (Gaius, Institutiones) against the Background of Contemporary Legal Solutions in the Republic of Poland: PERSONAE - Twarowska-Antczak, Emilia (Sensus Historiae, 2025)
The aim of the publication is to show the similarities and differences in the scope of the definition of a foreigner between contemporary solutions in Polish law and those in Roman law. Such research will allow for a broader reflection on the status of a foreigner in the territory of the Third Polish Republic. In this case, we are dealing with the continuity of the tradition of European law. Moreover, historical reflection indicates that the solutions of Roman law can be an inspiration for contemporary reforms in the scope of the status of foreigners, because despite the passage of centuries, Roman law was often surprisingly logical and functional.